2007
DOI: 10.1002/elps.200600742
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of enantioselective binding of antihistamines to human serum albumin by ACE

Abstract: The drug binding to plasma and tissue proteins is a fundamental factor in determining the overall pharmacological activity of a drug. HSA, together with alpha(1)-acid glycoprotein, are the most important plasma proteins, which act as drug carriers, with implications on the pharmacokinetic of drugs. Among plasma proteins, HSA possesses the highest enantioselectivity. In this paper, a new methodology for the study of enantiodifferentiation of chiral drugs with HSA is developed and applied to evaluate the possibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 14 publications
(21 reference statements)
1
19
0
Order By: Relevance
“…Ultrafiltration combined with chiral separation techniques (Table 1) has been used in the literature for evaluating the stereoselectivity in binding of bimoclomol to HSA, AGP and plasma ; alprenolol to AGP (Imamura et al, 2002) or the tryptophan to bovine serum albumin (BSA) (Randon et al, 2000); warfarin, phenprocoumon and acenocoumarol have been tested for their stereoselective binding to AGP (Hazai et al, 2006); mefloquine to HSA and AGP (Zsila et al, 2008); individual sulbenicillin enantiomers to HSA (Tsuda et al, 2001); ketoprofen to HSA (Lagrange et al, 2000); aminohydantoins in rat, dog and human plasma (Peng et al, 1999); dihydrodiazepam and lorazepam acetate to AGP (Fitos et al, 1995); carbenicillin to HSA (Itoh et al, 1996); antihistamines to HSA; and basic drugs to plasma (Martínez-Gómez et al, 2007a;2007b).…”
Section: Membrane-based Separation Techniquesmentioning
confidence: 99%
See 2 more Smart Citations
“…Ultrafiltration combined with chiral separation techniques (Table 1) has been used in the literature for evaluating the stereoselectivity in binding of bimoclomol to HSA, AGP and plasma ; alprenolol to AGP (Imamura et al, 2002) or the tryptophan to bovine serum albumin (BSA) (Randon et al, 2000); warfarin, phenprocoumon and acenocoumarol have been tested for their stereoselective binding to AGP (Hazai et al, 2006); mefloquine to HSA and AGP (Zsila et al, 2008); individual sulbenicillin enantiomers to HSA (Tsuda et al, 2001); ketoprofen to HSA (Lagrange et al, 2000); aminohydantoins in rat, dog and human plasma (Peng et al, 1999); dihydrodiazepam and lorazepam acetate to AGP (Fitos et al, 1995); carbenicillin to HSA (Itoh et al, 1996); antihistamines to HSA; and basic drugs to plasma (Martínez-Gómez et al, 2007a;2007b).…”
Section: Membrane-based Separation Techniquesmentioning
confidence: 99%
“…On the other hand, it was observed that degradation of (R)-sulbenicillin in the presence of HSA was faster than that of (S)-sulbenicillin. Martínez-Gómez et al (2007a) studied the enantioselective binding of the antihistamines brompheniramine, chlorpheniramine, hydroxyzine and orphenadrine to HSA. Owing to the high affinity of these drugs towards HSA, the authors proposed a procedure that includes (i) the ultrafiltration of preequilibrated samples containing HSA and the racemic drug, (ii) the treatment of the insoluble fraction obtained, which contains the bound fraction of drug, with an organic solvent to provoke the precipitation of proteins and the liberation of the 232 bound drug and (iii) the chiral separation and determination of enantiomers by ACE using HSA as chiral selector.…”
Section: Human Serum Albumin Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…(3d) allows evaluating competitive models, through Eq. (3d1) or (3d2) [6]. In order to avoid infra-or over-estimations on the parameters (by using only one of the equations) we have designed a SIMPLEX algorithm that simultaneously optimises both equations.…”
Section: Consistent and Inconsistent/insecure Approaches/estimatesmentioning
confidence: 99%
“…The majority of these methodologies include a first step in which the free drug fraction is separate from the bound drug once the drug-protein equilibrium has been reached using different techniques, such as the traditional equilibrium dialysis [3], ultracentrifugation [3] or ultrafiltration [4]. The second step includes chiral analysis of enantiomers in the unbound fraction using different techniques such as LC and CE and different chiral selectors, for instance using EKC [6].…”
Section: Introductionmentioning
confidence: 99%